Preparation method of foamed aluminum-based composite material for degrading sewage containing acid red G

CN119746936AActive Publication Date: 2025-04-04NORTH CHINA UNIVERSITY OF TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411950401.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to effectively degrade acid-containing red G sewage, and traditional methods are difficult to efficiently activate peracetic acid under visible light conditions.

Method used

By loading polygeminoxime-based aniline on the surface of the foam aluminum matrix, it is converted into [Sm(PAOAn)2(gly)2] coordination polymer, and then loading BiO9SmMo2 nanocrystals on its surface to form a foam aluminum matrix composite material, and the visible photocatalytic synergistic activation of peracetic acid and degrading acid-containing red G sewage.

Benefits of technology

This method significantly improves the visible photocatalytic characteristics and peracetic acid activation efficiency of foamed aluminum-based composite materials, and achieves efficient degradation of acid-containing red G sewage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746936A_ABST
    Figure CN119746936A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a foamed aluminum-based composite material for degrading sewage containing acid red G. The preparation method comprises the following steps: (1) loading polyamidoxime aniline on the surface of a foamed aluminum matrix; (2) converting the polyamidoxime aniline on the surface of the foamed aluminum matrix into a [Sm (PAOAn) 2 (gly) 2] coordination polymer; and step [3], loading the BiO9SmMo2 nanocrystals on the surface of the Sm (PAOAn) 2 (gly) 2 coordination polymer. The foamed aluminum-based composite material prepared by the method provided by the invention has outstanding visible light catalysis characteristic, and has the performance of degrading sewage containing acid red G by efficient visible light catalysis and synergistic activation of peracetic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acidic red G sewage treatment, in particular to a method for preparing a foamed aluminum-based composite material for photocatalytically synergistically activating peracetic acid to degrade acidic red G-containing sewage. Background Art

[0002] Acid Red G is an azo compound with two nitrogen atoms forming an azo bond (-N=N-) structure and a sulfonic acid group. The azo structure of Acid Red G gives it bright colors and excellent color fastness, and the sulfonic acid group of Acid Red G gives it a certain water solubility and stability in different acid and alkali chemical environments. Therefore, Acid Red G is widely used in dyeing, printing and textile industries as an azo dye. In the production process of Acid Red G in these industries, a considerable proportion of Acid Red G is discharged into the water environment, thereby generating a large amount of wastewater containing Acid Red G. Acid Red G has a certain solubility, stable chemical properties, is difficult to degrade naturally and biodegrade, and is easy to migrate. Acid Red G will be reduced to aromatic amine carcinogenic compounds after drinking acid red G-containing wastewater or reaching humans or animals through the food chain, posing a serious threat to humans and the natural environment.

[0003] After full activation, peracetic acid can generate acetoxyl radicals CH3C(O)O·, peroxyacetyl radicals CH3C(O)OO·, peroxyalkyl radicals OOCH3·, OH·hydroxyl radicals and singlet oxygen 1 O2 and other strong oxidizing substances, which can break the azo bond of acid red G, destroy the naphthalene ring structure of acid red G, and achieve effective degradation of acid red G-containing wastewater.

[0004] Therefore, there is an urgent need to develop a material with outstanding visible light photocatalytic properties and visible light photocatalytic efficient synergistic activation of peracetic acid for degrading acidic red G-containing wastewater. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater. The foamed aluminum-based composite material prepared by the method has outstanding visible light catalytic properties and has the performance of efficiently catalyzing visible light to synergistically activate peracetic acid to degrade acidic red G-containing wastewater.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] The present invention provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, comprising the following steps:

[0008] Step [1]: loading polyamidoaniline on the surface of the foamed aluminum substrate;

[0009] Step [2] converting the polyamidoaniline on the surface of the foam aluminum substrate into a [Sm(PAOAn)2(gly)2] coordination polymer;

[0010] Step [3] Loading BiO9SmMo2 nanocrystals on the surface of Sm(PAOAn)2(gly)2 coordination polymer.

[0011] Preferably, the step [1] specifically includes the following operations:

[0012] a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution; immerse the aluminum foam sample in the reaction solution and react at room temperature for 10-14 hours. After removing the sample, wash it with deionized water to obtain an aluminum foam with polyaniline loaded on the surface, which is recorded as intermediate A;

[0013] a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite to deionized water and mix to form a synthetic solution; immerse the intermediate A in the synthetic solution and react at room temperature for 8-10 hours. After taking out the sample, wash it with deionized water and dry it at 30-40°C for 4-6 hours to obtain a foamed aluminum with polyamidoaniline loaded on the surface, which is recorded as intermediate B.

[0014] Preferably, in step a1, the amount of phenylacetic acid added per liter of the reaction solution is 80-150 g, the amount of urea added is 40-70 g, the amount of ammonium bicarbonate added is 50-80 g, and the amount of ammonium persulfate added is 10-20 g; the weight of the foamed aluminum immersed in each liter of the reaction solution is 20-40 g.

[0015] Preferably, in step a2, the amount of cyanoacetic acid added to each liter of the synthetic liquid is 40-70 g, the amount of hydroxylamine added is 20-50 g, and the amount of ammonium nitrite added is 10-20 g; the weight of the intermediate A immersed in each liter of the synthetic liquid is 60-110 g.

[0016] Preferably, the step [2] specifically includes the following operations:

[0017] b1. Add aminoacetic acid, samarium nitrate and sodium periodate to deionized water, mix to form a solution, heat to 70-110 ° C, react for 3-5 hours, filter to obtain a solid product, and dry the solid product at 40-60 ° C for 3-4 hours to obtain a solid precursor;

[0018] b2. Add aniline, aminoacetic acid, samarium nitrate, sodium perborate and the solid phase precursor into deionized water and mix to form a preparation solution; immerse the intermediate B in the preparation solution, heat it in a water bath to 40-60°C, react for 8-10 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 10-14 hours to obtain foamed aluminum with a surface loaded with [Sm(PAOAn)2(gly)2] coordination polymer, which is recorded as intermediate C.

[0019] Preferably, in step b1, the amount of aminoacetic acid added to each liter of the generated liquid is 100-140 g, the amount of samarium nitrate added is 40-70 g, and the amount of sodium periodate added is 5-15 g.

[0020] Preferably, in step b2, the amount of aniline added per liter of the preparation solution is 40-60 ml, the amount of aminoacetic acid added is 30-60 g, the amount of samarium nitrate added is 20-40 g, the amount of sodium perborate added is 5-15 g, and the amount of solid phase precursor added is 80-120 g; the weight of the intermediate B immersed in each liter of the preparation solution is 90-120 g.

[0021] Preferably, the step [3] specifically includes the following operations:

[0022] c1. Add bismuth telluride and samarium chloride to ethanol and mix to form an organic liquid; add molybdic acid and 68% concentrated nitric acid by mass to deionized water and mix to form an inorganic liquid; mix the organic liquid and the inorganic liquid in a certain proportion to form a crystallization liquid,

[0023] c2. Immerse the intermediate C in the crystallization solution, react at room temperature for 24-30 hours, take out the sample and wash it with deionized water, dry it at 50-60°C for 3-6 hours, complete the loading of BiO9SmMo2 nanocrystals on the surface of [Sm(PAOAn)2(gly)2] coordination polymer, and finally obtain the foam aluminum-based composite material.

[0024] Preferably, in step c1, the amount of bismuth telluride added to each liter of the organic liquid is 40-60 g, and the amount of samarium chloride added is 30-50 g; the amount of molybdic acid added to each liter of the inorganic liquid is 15-40 g, and the mass fraction of nitric acid in the inorganic liquid is 4-8%; the volume ratio between the organic liquid and the inorganic liquid in the crystallization liquid is 3-5:6-9.

[0025] Preferably, in step c2, the weight of the intermediate C immersed in each liter of the crystallization solution is 120-140 g.

[0026] The positive effects of the present invention are as follows: the foam aluminum-based composite material prepared according to the method of the present invention is firstly based on the formation of polyamidoaniline (PAOAn) organic matter on the surface of the foam aluminum matrix, the nitrogen atom of the NH2 group of the polyamidoaniline (PAOAn) organic matter provides a lone pair of electrons to share with the samarium ion, and the O atom of the aminoacetate (gly) group and the nitrogen atom of the NH2 group share with the samarium ion to form a [Sm(PAOAn)2(gly)2] coordination polymer with a connecting structure, and then BiO9SmMo2 alloy nanoparticles are loaded on the surface of the [Sm(PAOAn)2(gly)2] coordination polymer. Among them, under the conditions of the action of the nitrogen atom of the NH2 group of the amidoxime group of the [Sm(PAOAn)2(gly)2] coordination polymer and the O atom and the nitrogen atom of the NH2 group of the aminoacetate (gly) group with samarium ions, acid red G has a strong adsorption effect, and the organic matter of polyamidoaniline (PAOAn) has good light absorption performance in the visible light region; at the same time, the BiO9SmMo2 crystal is an orthorhombic system with a space group of Pnma (62). The BiO9SmMo2 alloy nanoparticles have a strong adsorption effect on the Bi, Sm and The orbital hybridization form of Mo and oxygen has a narrow bandgap and good visible light response ability; in addition, the interface energy between the [Sm(PAOAn)2(gly)2] coordination polymer and the BiO9SmMo2 alloy nanoparticles can enhance the generation of visible light photogenerated electrons and holes, thereby reducing the activation energy of peracetic acid, thereby promoting the generation of CH3C(O)OO·, CH3C(O)O· and ·OH free radicals, which are used to break the azo bond of acid red G and destroy the naphthalene ring structure of acid red G, thereby achieving effective degradation of acid red G-containing wastewater.

[0027] In summary, the foamed aluminum-based composite material prepared according to the present invention has outstanding visible light catalytic properties and has the performance of highly efficient visible light catalytic synergistic activation of peracetic acid to degrade acidic red G-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the preparation process of the foamed aluminum-based composite material of the present invention;

[0029] Figure 2 Schematic diagram of the microstructure of the foamed aluminum-based composite material of the present invention;

[0030] Figure 3 is the relative concentration of residual acid red G in the simulated acid red G-containing wastewater treated under different conditions in Example 1 of the present invention;

[0031] Figure 4 is the relative concentration of residual acid red G in the simulated acid red G-containing wastewater treated under different conditions in Comparative Example 1 of the present invention;

[0032] Figure 5It is the relative concentration of residual acid red G in the simulated acid red G-containing wastewater treated under different conditions in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0033] Reference Figure 1 The present invention provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, comprising the following steps:

[0034] Step [1] loading polyamidoaniline on the surface of the foamed aluminum substrate specifically comprises the following operations:

[0035] a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution, wherein the amount of phenylacetic acid added to each liter of the reaction solution is 80-150 g, the amount of urea added is 40-70 g, the amount of ammonium bicarbonate added is 50-80 g, and the amount of ammonium persulfate added is 10-20 g; immerse the foamed aluminum sample in the reaction solution (the weight of the foamed aluminum immersed in each liter of the reaction solution is 20-40 g), react at room temperature for 10-14 hours, take out the sample and wash it with deionized water to obtain foamed aluminum with polyaniline loaded on the surface, which is recorded as intermediate A;

[0036] a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite to deionized water and mix to form a synthetic solution, wherein the amount of cyanoacetic acid added to each liter of the synthetic solution is 40-70 g, the amount of hydroxylamine added is 20-50 g, and the amount of ammonium nitrite added is 10-20 g; immerse the intermediate A in the synthetic solution (the weight of the intermediate A immersed in each liter of the synthetic solution is 60-110 g), react at room temperature for 8-10 hours, take out the sample and wash it with deionized water, dry it at 30-40°C for 4-6 hours, and obtain a foamed aluminum with polyamidoaniline on the surface, which is recorded as intermediate B; wherein the structural formula of the polyamidoaniline (PAOAn) is:

[0037]

[0038] Step [2] converts the polyamidoaniline on the surface of the foam aluminum substrate into a [Sm(PAOAn)2(gly)2] coordination polymer, specifically comprising the following operations:

[0039] b1. Add aminoacetic acid, samarium nitrate and sodium periodate to deionized water and mix to form a generated solution (the amount of aminoacetic acid added per liter of the generated solution is 100 to 140 g, the amount of samarium nitrate added is 40 to 70 g, and the amount of sodium periodate added is 5 to 15 g), heated to 70-110 ° C, reacted for 3-5 hours, filtered to obtain a solid product, and the solid product was dried at 40-60 ° C for 3-4 hours to obtain a solid precursor;

[0040] b2. Add aniline, aminoacetic acid, samarium nitrate, sodium perborate and the solid phase precursor to deionized water and mix to form a preparation solution, wherein the amount of aniline added per liter of the preparation solution is 40-60 ml, the amount of aminoacetic acid added is 30-60 g, the amount of samarium nitrate added is 20-40 g, the amount of sodium perborate added is 5-15 g, and the amount of solid phase precursor added is 80-120 g; immerse the intermediate B in the preparation solution (the weight of the intermediate B immersed in each liter of the preparation solution is 90-120 g), heat in a water bath to 40-60 ° C, react for 8-10 hours, remove the sample and wash it with deionized water, dry it at room temperature for 10-14 hours, and obtain a foamed aluminum with a surface loaded with [Sm(PAOAn)2(gly)2] coordination polymer, recorded as intermediate C; wherein the structural formula of the [Sm(PAOAn)2(gly)2] coordination polymer is:

[0041]

[0042] Step [3] loading BiO9SmMo2 nanocrystals on the surface of the Sm(PAOAn)2(gly)2 coordination polymer, specifically comprising the following operations:

[0043] c1. Add bismuth telluride and samarium chloride to ethanol and mix to form an organic liquid (the amount of bismuth telluride added to the organic liquid is 40 to 60 g, and the amount of samarium chloride added is 30 to 50 g per liter); add molybdic acid and 68% concentrated nitric acid by mass to deionized water and mix to form an inorganic liquid (the amount of molybdic acid added to the inorganic liquid is 15 to 40 g per liter, and the mass fraction of nitric acid in the inorganic liquid is 4 to 8%); mix the organic liquid and the inorganic liquid in a volume ratio of 3 to 5:6 to 9 to form a crystallization liquid,

[0044] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 120-140g), reacted at room temperature for 24-30 hours, and the sample is taken out and washed with deionized water, and dried at 50-60°C for 3-6 hours to complete the loading of BiO9SmMo2 nanocrystals on the surface of [Sm(PAOAn)2(gly)2] coordination polymer, and finally the foam aluminum-based composite material (foam aluminum [Sm(PAOAn)2(gly)2] coordination polymer / BiO9SmMo2 alloy nanocrystals) is obtained. The microstructure schematic diagram is shown as follows Figure 2 shown.

[0045] The preferred embodiments of the present invention are described below by way of example.

[0046] Example 1

[0047] Preferred embodiment 1 of the present invention provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, comprising the following steps:

[0048] Step [1] loading polyamidoaniline on the surface of the foamed aluminum substrate specifically comprises the following operations:

[0049] a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution, wherein the amount of phenylacetic acid added per liter of the reaction solution is 120 g, the amount of urea added is 60 g, the amount of ammonium bicarbonate added is 70 g, and the amount of ammonium persulfate added is 18 g; immerse the foamed aluminum sample in the reaction solution (the weight of the foamed aluminum immersed in each liter of the reaction solution is 35 g), react at room temperature for 13 hours, take out the sample and wash it with deionized water to obtain foamed aluminum with polyaniline loaded on the surface, which is recorded as intermediate A;

[0050] a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite into deionized water and mix to form a synthetic solution, wherein the amount of cyanoacetic acid added to each liter of the synthetic solution is 60 g, the amount of hydroxylamine added is 40 g, and the amount of ammonium nitrite added is 15 g; immerse the intermediate A in the synthetic solution (the weight of the intermediate A immersed in each liter of the synthetic solution is 90 g), react at room temperature for 9 hours, take out the sample, wash it with deionized water, and dry it at 40°C for 5 hours to obtain foamed aluminum with polyamidoaniline loaded on the surface, which is recorded as intermediate B.

[0051] Step [2] converts the polyamidoaniline on the surface of the foam aluminum substrate into a [Sm(PAOAn)2(gly)2] coordination polymer, specifically comprising the following operations:

[0052] b1. Add aminoacetic acid, samarium nitrate and sodium periodate to deionized water and mix to form a generated solution (the amount of aminoacetic acid added per liter of the generated solution is 130 g, the amount of samarium nitrate added is 60 g, and the amount of sodium periodate added is 10 g), heated to 80 ° C, reacted for 4 hours, filtered to obtain a solid product, and the solid product was dried at 50 ° C for 4 hours to obtain a solid precursor;

[0053] b2. Add aniline, aminoacetic acid, samarium nitrate, sodium perborate and the solid phase precursor to deionized water and mix to form a preparation solution, wherein per liter of the preparation solution, the amount of aniline added is 50 ml, the amount of aminoacetic acid added is 50 g, the amount of samarium nitrate added is 30 g, the amount of sodium perborate added is 10 g, and the amount of solid phase precursor added is 110 g; immerse the intermediate B in the preparation solution (the weight of the intermediate B immersed in each liter of the preparation solution is 100 g), heat to 55°C in a water bath, react for 9 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 12 hours to obtain foamed aluminum with a surface loaded with [Sm(PAOAn)2(gly)2] coordination polymer, recorded as intermediate C.

[0054] Step [3] loading BiO9SmMo2 nanocrystals on the surface of the Sm(PAOAn)2(gly)2 coordination polymer, specifically comprising the following operations:

[0055] c1. Add bismuth telluride and samarium chloride to ethanol and mix to form an organic liquid (the amount of bismuth telluride added to each liter of the organic liquid is 50 g, and the amount of samarium chloride added is 45 g); add molybdic acid and 68% concentrated nitric acid by mass to deionized water and mix to form an inorganic liquid (the amount of molybdic acid added to each liter of the inorganic liquid is 30 g, and the mass fraction of nitric acid in the inorganic liquid is 6%); mix the organic liquid and the inorganic liquid in a volume ratio of 5:7 to form a crystallization liquid,

[0056] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 130 g), reacted at room temperature for 26 hours, and the sample is taken out and washed with deionized water, and dried at 54°C for 5 hours to complete the loading of BiO9SmMo2 nanocrystals on the surface of the [Sm(PAOAn)2(gly)2] coordination polymer, and finally the foam aluminum-based composite material (foam aluminum [Sm(PAOAn)2(gly)2] coordination polymer / BiO9SmMo2 alloy nanocrystals) is obtained, which is recorded as Example 1.

[0057] Comparative Example 1

[0058] This comparative example 1 provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, comprising the following steps:

[0059] Step [1] loading polyamidoaniline on the surface of the foamed aluminum substrate specifically comprises the following operations:

[0060] a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution, wherein the amount of phenylacetic acid added per liter of the reaction solution is 90 g, the amount of urea added is 60 g, the amount of ammonium bicarbonate added is 60 g, and the amount of ammonium persulfate added is 12 g; immerse the foamed aluminum sample in the reaction solution (the weight of the foamed aluminum immersed in each liter of the reaction solution is 25 g), react at room temperature for 11 hours, take out the sample and wash it with deionized water to obtain foamed aluminum with polyaniline loaded on the surface, which is recorded as intermediate A;

[0061] a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite into deionized water and mix to form a synthetic solution, wherein the amount of cyanoacetic acid added to each liter of the synthetic solution is 50 g, the amount of hydroxylamine added is 30 g, and the amount of ammonium nitrite added is 15 g; immerse the intermediate A in the synthetic solution (the weight of the intermediate A immersed in each liter of the synthetic solution is 70 g), react at room temperature for 9 hours, take out the sample, wash it with deionized water, and dry it at 35°C for 5 hours to obtain foamed aluminum with polyamidoaniline loaded on the surface, which is recorded as intermediate B.

[0062] Step [2] converts the polyamidoaniline on the surface of the foam aluminum substrate into a [Sm(PAOAn)2(gly)2] coordination polymer, specifically comprising the following operations:

[0063] b1. Add aminoacetic acid, samarium nitrate and sodium periodate to deionized water and mix to form a generated solution (the amount of aminoacetic acid added per liter of the generated solution is 120 g, the amount of samarium nitrate added is 50 g, and the amount of sodium periodate added is 7 g), heated to 75 ° C, reacted for 4 hours, filtered to obtain a solid product, and the solid product was dried at 50 ° C for 3 hours to obtain a solid precursor;

[0064] b2. Add aniline, aminoacetic acid, samarium nitrate, sodium perborate and the solid phase precursor to deionized water and mix to form a preparation solution, wherein per liter of the preparation solution, the amount of aniline added is 45 ml, the amount of aminoacetic acid added is 40 g, the amount of samarium nitrate added is 25 g, the amount of sodium perborate added is 7 g, and the amount of solid phase precursor added is 100 g; immerse the intermediate B in the preparation solution (the weight of the intermediate B immersed in each liter of the preparation solution is 100 g), heat to 50°C in a water bath, react for 9 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 12 hours to obtain a foamed aluminum with a surface loaded with [Sm(PAOAn)2(gly)2] coordination polymer, which is recorded as Comparative Example 1.

[0065] Comparative Example 2

[0066] This comparative example 2 provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, comprising the following steps:

[0067] Step [1] loading polyamidoaniline on the surface of the foamed aluminum substrate specifically comprises the following operations:

[0068] a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution, wherein the amount of phenylacetic acid added per liter of the reaction solution is 110 g, the amount of urea added is 60 g, the amount of ammonium bicarbonate added is 70 g, and the amount of ammonium persulfate added is 14 g; immerse the foamed aluminum sample in the reaction solution (the weight of the foamed aluminum immersed in each liter of the reaction solution is 24 g), react at room temperature for 12 hours, take out the sample and wash it with deionized water to obtain foamed aluminum with polyaniline loaded on the surface, which is recorded as intermediate A;

[0069] a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite into deionized water and mix to form a synthetic solution, wherein the amount of cyanoacetic acid added to each liter of the synthetic solution is 45 g, the amount of hydroxylamine added is 30 g, and the amount of ammonium nitrite added is 15 g; immerse the intermediate A in the synthetic solution (the weight of the intermediate A immersed in each liter of the synthetic solution is 80 g), react at room temperature for 9 hours, take out the sample, wash it with deionized water, and dry it at 35°C for 5 hours to obtain foamed aluminum with polyamidoaniline loaded on the surface, which is recorded as intermediate B.

[0070] Step [2] loading BiO9SmMo2 nanocrystals on the surface of polyamidoaniline, specifically comprising the following operations:

[0071] c1. Add bismuth telluride and samarium chloride to ethanol and mix to form an organic liquid (the amount of bismuth telluride added to each liter of the organic liquid is 45 g, and the amount of samarium chloride added is 40 g); add molybdic acid and 68% concentrated nitric acid by mass to deionized water and mix to form an inorganic liquid (the amount of molybdic acid added to each liter of the inorganic liquid is 20 g, and the mass fraction of nitric acid in the inorganic liquid is 5%); mix the organic liquid and the inorganic liquid in a volume ratio of 3 to 5:6 to 9 to form a crystallization liquid,

[0072] c2. The intermediate B is immersed in the crystallization solution (the weight of the intermediate B immersed in each liter of the crystallization solution is 125 g), reacted at room temperature for 24 hours, and the sample is taken out and washed with deionized water, and dried at 55° C. for 5 hours to complete the loading of BiO9SmMo2 nanocrystals on the surface of polyamidoaniline, and finally the foamed aluminum-based composite material (foamed aluminum polyamidoaniline / BiO9SmMo2 alloy nanocrystals) is obtained, which is recorded as Comparative Example 2.

[0073] In order to analyze the visible light catalytic properties of Example 1, Comparative Example 1 and Comparative Example 2 and the performance of visible light catalytic synergistic activation of peracetic acid in degrading acidic red G-containing wastewater, acidic red G was added to deionized water to form simulated acidic red G-containing wastewater with an acidic red G concentration of 50 mg / L. 100 ml of simulated acidic red G-containing wastewater was poured into beakers respectively, 20 g of Example 1, Comparative Example 1 and Comparative Example 2 were placed into beakers respectively, a peracetic acid solution with a mass concentration of 15% was added to the simulated acidic red G-containing wastewater, and the amount of peracetic acid added was 300 μmol / L, and a 500W xenon lamp light source was used to irradiate Comparative Example 1, Comparative Example 2 and Example 1 for 40 minutes under visible light with a wavelength of 480 nm, and the residual acidic red G concentration in the degradation process of acidic red G-containing wastewater was measured with a UV-visible spectrophotometer (simultaneously, a control group with only light and a control group without light was set), and the results are as follows: Figure 3-5As shown in the figure, it can be seen that the relative residual acid red G concentration of the acid red G-containing wastewater degraded by Example 1 under visible light synergistically activated peracetic acid is only 0.06, which is significantly lower than the relative residual acid red G concentrations of the acid red G-containing wastewater degraded by Comparative Example 1 and Comparative Example 2 under the same conditions (0.32 and 0.41, respectively). In addition, even under the condition of only visible light irradiation without the addition of peracetic acid, the relative residual acid red G concentration of the acid red G-containing wastewater degraded by Example 1 is only 0.48, which is significantly lower than the relative residual acid red G concentrations of Comparative Example 1 and Comparative Example 2 under the same conditions (0.73 and 0.81). It can be seen that Example 1 has outstanding photocatalytic properties.

[0074] In summary, the foamed aluminum-based composite material prepared according to the present invention has outstanding visible light catalytic properties, and has the performance of highly efficient visible light catalytic synergistic activation of peracetic acid to degrade acidic red G-containing wastewater.

[0075] To illustrate in further detail, three additional examples are provided below.

[0076] Example 2

[0077] Preferred embodiment 2 of the present invention provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, comprising the following steps:

[0078] Step [1] loading polyamidoaniline on the surface of the foamed aluminum substrate specifically comprises the following operations:

[0079] a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution, wherein the amount of phenylacetic acid added to each liter of the reaction solution is 80 g, the amount of urea added is 70 g, the amount of ammonium bicarbonate added is 50 g, and the amount of ammonium persulfate added is 20 g; immerse the foamed aluminum sample in the reaction solution (the weight of the foamed aluminum immersed in each liter of the reaction solution is 20 g), react at room temperature for 10 hours, take out the sample and wash it with deionized water to obtain foamed aluminum with polyaniline loaded on the surface, which is recorded as intermediate A;

[0080] a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite into deionized water and mix to form a synthetic solution, wherein the amount of cyanoacetic acid added to each liter of the synthetic solution is 40 g, the amount of hydroxylamine added is 50 g, and the amount of ammonium nitrite added is 20 g; immerse the intermediate A in the synthetic solution (the weight of the intermediate A immersed in each liter of the synthetic solution is 60 g), react at room temperature for 8 hours, take out the sample, wash it with deionized water, and dry it at 30°C for 6 hours to obtain foamed aluminum with polyamidoaniline loaded on the surface, which is recorded as intermediate B.

[0081] Step [2] converts the polyamidoaniline on the surface of the foam aluminum substrate into a [Sm(PAOAn)2(gly)2] coordination polymer, specifically comprising the following operations:

[0082] b1. Add aminoacetic acid, samarium nitrate and sodium periodate to deionized water and mix to form a generated solution (the amount of aminoacetic acid added per liter of the generated solution is 100 g, the amount of samarium nitrate added is 70 g, and the amount of sodium periodate added is 5 g), heated to 70 ° C, reacted for 5 hours, filtered to obtain a solid product, and the solid product was dried at 60 ° C for 3 hours to obtain a solid precursor;

[0083] b2. Add aniline, aminoacetic acid, samarium nitrate, sodium perborate and the solid-phase precursor to deionized water and mix to form a preparation solution, wherein per liter of the preparation solution, the amount of aniline added is 60 ml, the amount of aminoacetic acid added is 30 g, the amount of samarium nitrate added is 20 g, the amount of sodium perborate added is 5 g, and the amount of solid-phase precursor added is 80 g; immerse the intermediate B in the preparation solution (the weight of the intermediate B immersed in each liter of the preparation solution is 90 g), heat to 60°C in a water bath, react for 8 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 10 hours to obtain foamed aluminum with a surface loaded with [Sm(PAOAn)2(gly)2] coordination polymer, recorded as intermediate C.

[0084] Step [3] loading BiO9SmMo2 nanocrystals on the surface of the Sm(PAOAn)2(gly)2 coordination polymer, specifically comprising the following operations:

[0085] c1. Add bismuth telluride and samarium chloride to ethanol and mix to form an organic liquid (the amount of bismuth telluride added to each liter of the organic liquid is 60 g, and the amount of samarium chloride added is 50 g); add molybdic acid and 68% concentrated nitric acid by mass to deionized water and mix to form an inorganic liquid (the amount of molybdic acid added to each liter of the inorganic liquid is 15 g, and the mass fraction of nitric acid in the inorganic liquid is 4%); mix the organic liquid and the inorganic liquid in a volume ratio of 5:6 to form a crystallization liquid,

[0086] c2. Immerse the intermediate C in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 120 g), react at room temperature for 24 hours, take out the sample and wash it with deionized water, dry it at 50°C for 6 hours, complete the loading of BiO9SmMo2 nanocrystals on the surface of [Sm(PAOAn)2(gly)2] coordination polymer, and finally obtain the foam aluminum-based composite material (foam aluminum [Sm(PAOAn)2(gly)2] coordination polymer / BiO9SmMo2 alloy nanocrystals).

[0087] Example 3

[0088] Preferred embodiment 3 of the present invention provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, comprising the following steps:

[0089] Step [1] loading polyamidoaniline on the surface of the foamed aluminum substrate specifically comprises the following operations:

[0090] a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution, wherein the amount of phenylacetic acid added per liter of the reaction solution is 150 g, the amount of urea added is 40 g, the amount of ammonium bicarbonate added is 80 g, and the amount of ammonium persulfate added is 10 g; immerse the foamed aluminum sample in the reaction solution (the weight of the foamed aluminum immersed in each liter of the reaction solution is 40 g), react at room temperature for 14 hours, take out the sample and wash it with deionized water to obtain foamed aluminum with polyaniline loaded on the surface, which is recorded as intermediate A;

[0091] a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite into deionized water and mix to form a synthetic solution, wherein the amount of cyanoacetic acid added to each liter of the synthetic solution is 70 g, the amount of hydroxylamine added is 20 g, and the amount of ammonium nitrite added is 10 g; immerse the intermediate A in the synthetic solution (the weight of the intermediate A immersed in each liter of the synthetic solution is 110 g), react at room temperature for 10 hours, take out the sample, wash it with deionized water, and dry it at 40°C for 4 hours to obtain foamed aluminum with polyamidoaniline loaded on the surface, which is recorded as intermediate B.

[0092] Step [2] converts the polyamidoaniline on the surface of the foam aluminum substrate into a [Sm(PAOAn)2(gly)2] coordination polymer, specifically comprising the following operations:

[0093] b1. Add aminoacetic acid, samarium nitrate and sodium periodate to deionized water and mix to form a generated solution (the amount of aminoacetic acid added per liter of the generated solution is 140 g, the amount of samarium nitrate added is 40 g, and the amount of sodium periodate added is 15 g), heated to 110 ° C, reacted for 3 hours, filtered to obtain a solid product, and the solid product was dried at 40 ° C for 4 hours to obtain a solid precursor;

[0094] b2. Add aniline, aminoacetic acid, samarium nitrate, sodium perborate and the solid phase precursor into deionized water and mix to form a preparation solution, wherein per liter of the preparation solution, the amount of aniline added is 40 ml, the amount of aminoacetic acid added is 60 g, the amount of samarium nitrate added is 40 g, the amount of sodium perborate added is 15 g, and the amount of solid phase precursor added is 120 g; immerse the intermediate B in the preparation solution (the weight of the intermediate B immersed in each liter of the preparation solution is 120 g), heat to 40°C in a water bath, react for 10 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 14 hours to obtain foamed aluminum with a surface loaded with [Sm(PAOAn)2(gly)2] coordination polymer, recorded as intermediate C.

[0095] Step [3] loading BiO9SmMo2 nanocrystals on the surface of the Sm(PAOAn)2(gly)2 coordination polymer, specifically comprising the following operations:

[0096] c1. Add bismuth telluride and samarium chloride to ethanol and mix to form an organic liquid (the amount of bismuth telluride added to each liter of the organic liquid is 40 g, and the amount of samarium chloride added is 30 g); add molybdic acid and 68% concentrated nitric acid by mass to deionized water and mix to form an inorganic liquid (the amount of molybdic acid added to each liter of the inorganic liquid is 40 g, and the mass fraction of nitric acid in the inorganic liquid is 8%); mix the organic liquid and the inorganic liquid in a volume ratio of 3:7 to form a crystallization liquid,

[0097] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 140 g), reacted at room temperature for 30 hours, and the sample is taken out and washed with deionized water, and dried at 60°C for 3 hours to complete the loading of BiO9SmMo2 nanocrystals on the surface of the [Sm(PAOAn)2(gly)2] coordination polymer, and finally the foam aluminum-based composite material (foam aluminum [Sm(PAOAn)2(gly)2] coordination polymer / BiO9SmMo2 alloy nanocrystals) is obtained.

[0098] Example 4

[0099] Preferred embodiment 4 of the present invention provides a method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, comprising the following steps:

[0100] Step [1] loading polyamidoaniline on the surface of the foamed aluminum substrate specifically comprises the following operations:

[0101] a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution, wherein the amount of phenylacetic acid added per liter of the reaction solution is 115 g, the amount of urea added is 55 g, the amount of ammonium bicarbonate added is 65 g, and the amount of ammonium persulfate added is 15 g; immerse the foamed aluminum sample in the reaction solution (the weight of the foamed aluminum immersed in each liter of the reaction solution is 30 g), react at room temperature for 12 hours, take out the sample and wash it with deionized water to obtain foamed aluminum with polyaniline loaded on the surface, which is recorded as intermediate A;

[0102] a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite into deionized water and mix to form a synthetic solution, wherein the amount of cyanoacetic acid added to each liter of the synthetic solution is 55 g, the amount of hydroxylamine added is 35 g, and the amount of ammonium nitrite added is 15 g; immerse the intermediate A in the synthetic solution (the weight of the intermediate A immersed in each liter of the synthetic solution is 85 g), react at room temperature for 9 hours, take out the sample, wash it with deionized water, and dry it at 35°C for 5 hours to obtain foamed aluminum with polyamidoaniline loaded on the surface, which is recorded as intermediate B.

[0103] Step [2] converts the polyamidoaniline on the surface of the foam aluminum substrate into a [Sm(PAOAn)2(gly)2] coordination polymer, specifically comprising the following operations:

[0104] b1. Add aminoacetic acid, samarium nitrate and sodium periodate to deionized water and mix to form a generated solution (the amount of aminoacetic acid added per liter of the generated solution is 120 g, the amount of samarium nitrate added is 55 g, and the amount of sodium periodate added is 10 g), heated to 90 ° C, reacted for 4 hours, filtered to obtain a solid product, and the solid product was dried at 50 ° C for 3.5 hours to obtain a solid precursor;

[0105] b2. Add aniline, aminoacetic acid, samarium nitrate, sodium perborate and the solid phase precursor into deionized water and mix to form a preparation solution, wherein per liter of the preparation solution, the amount of aniline added is 50 ml, the amount of aminoacetic acid added is 45 g, the amount of samarium nitrate added is 30 g, the amount of sodium perborate added is 10 g, and the amount of solid phase precursor added is 100 g; immerse the intermediate B in the preparation solution (the weight of the intermediate B immersed in each liter of the preparation solution is 105 g), heat to 50°C in a water bath, react for 9 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 12 hours to obtain foamed aluminum with a surface loaded with [Sm(PAOAn)2(gly)2] coordination polymer, recorded as intermediate C.

[0106] Step [3] loading BiO9SmMo2 nanocrystals on the surface of the Sm(PAOAn)2(gly)2 coordination polymer, specifically comprising the following operations:

[0107] c1. Add bismuth telluride and samarium chloride to ethanol and mix to form an organic liquid (the amount of bismuth telluride added to each liter of the organic liquid is 50 g, and the amount of samarium chloride added is 40 g); add molybdic acid and 68% concentrated nitric acid by mass to deionized water and mix to form an inorganic liquid (the amount of molybdic acid added to each liter of the inorganic liquid is 29 g, and the mass fraction of nitric acid in the inorganic liquid is 6%); mix the organic liquid and the inorganic liquid in a volume ratio of 4:7 to form a crystallization liquid,

[0108] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 130 g), reacted at room temperature for 27 hours, and the sample is taken out and washed with deionized water, and dried at 55°C for 4.5 hours to complete the loading of BiO9SmMo2 nanocrystals on the surface of the [Sm(PAOAn)2(gly)2] coordination polymer, and finally the foam aluminum-based composite material (foam aluminum [Sm(PAOAn)2(gly)2] coordination polymer / BiO9SmMo2 alloy nanocrystals) is obtained.

[0109] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater, characterized in that: The following steps are included: Step [1]: loading polyamidoaniline on the surface of the foamed aluminum substrate; Step [2] converting the polyamidoaniline on the surface of the foam aluminum substrate into a [Sm(PAOAn)2(gly)2] coordination polymer; Step [3] Loading BiO9SmMo2 nanocrystals on the surface of Sm(PAOAn)2(gly)2 coordination polymer.

2. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Add phenylacetic acid, urea, ammonium bicarbonate and ammonium persulfate to deionized water and mix to form a reaction solution; immerse the aluminum foam sample in the reaction solution and react at room temperature for 10-14 hours. After removing the sample, wash it with deionized water to obtain an aluminum foam with polyaniline loaded on the surface, which is recorded as intermediate A; a2. Add cyanoacetic acid, hydroxylamine and ammonium nitrite to deionized water and mix to form a synthetic solution; immerse the intermediate A in the synthetic solution and react at room temperature for 8-10 hours. After taking out the sample, wash it with deionized water and dry it at 30-40°C for 4-6 hours to obtain a foamed aluminum with polyamidoaniline loaded on the surface, which is recorded as intermediate B.

3. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 2, characterized in that: In step a1, the amount of phenylacetic acid added per liter of the reaction solution is 80-150 g, the amount of urea added is 40-70 g, the amount of ammonium bicarbonate added is 50-80 g, and the amount of ammonium persulfate added is 10-20 g; the weight of the foamed aluminum immersed in each liter of the reaction solution is 20-40 g.

4. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 2, characterized in that: In step a2, the amount of cyanoacetic acid added to each liter of the synthetic liquid is 40-70 g, the amount of hydroxylamine added is 20-50 g, and the amount of ammonium nitrite added is 10-20 g; the weight of the intermediate A immersed in each liter of the synthetic liquid is 60-110 g.

5. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add aminoacetic acid, samarium nitrate and sodium periodate to deionized water, mix to form a solution, heat to 70-110 ° C, react for 3-5 hours, filter to obtain a solid product, and dry the solid product at 40-60 ° C for 3-4 hours to obtain a solid precursor; b2. Add aniline, aminoacetic acid, samarium nitrate, sodium perborate and the solid phase precursor into deionized water and mix to form a preparation solution; immerse the intermediate B in the preparation solution, heat it in a water bath to 40-60°C, react for 8-10 hours, take out the sample, wash it with deionized water, and dry it at room temperature for 10-14 hours to obtain foamed aluminum with a surface loaded with [Sm(PAOAn)2(gly)2] coordination polymer, which is recorded as intermediate C.

6. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 5, characterized in that: In step b1, the amount of aminoacetic acid added to each liter of the generated liquid is 100-140 g, the amount of samarium nitrate added is 40-70 g, and the amount of sodium periodate added is 5-15 g.

7. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 5, characterized in that: In step b2, the amount of aniline added per liter of the preparation solution is 40-60 ml, the amount of aminoacetic acid added is 30-60 g, the amount of samarium nitrate added is 20-40 g, the amount of sodium perborate added is 5-15 g, and the amount of solid phase precursor added is 80-120 g; the weight of the intermediate B immersed in each liter of the preparation solution is 90-120 g.

8. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Add bismuth telluride and samarium chloride to ethanol and mix to form an organic liquid; add molybdic acid and 68% concentrated nitric acid by mass to deionized water and mix to form an inorganic liquid; mix the organic liquid and the inorganic liquid in a certain proportion to form a crystallization liquid, c2. Immerse the intermediate C in the crystallization solution, react at room temperature for 24-30 hours, take out the sample and wash it with deionized water, dry it at 50-60°C for 3-6 hours, complete the loading of BiO9SmMo2 nanocrystals on the surface of [Sm(PAOAn)2(gly)2] coordination polymer, and finally obtain the foam aluminum-based composite material.

9. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 8, characterized in that: In step c1, the amount of bismuth telluride added to each liter of the organic liquid is 40-60 g, and the amount of samarium chloride added is 30-50 g; the amount of molybdic acid added to each liter of the inorganic liquid is 15-40 g, and the mass fraction of nitric acid in the inorganic liquid is 4-8%; the volume ratio between the organic liquid and the inorganic liquid in the crystallization liquid is 3-5:6-9.

10. The method for preparing a foamed aluminum-based composite material for degrading acidic red G-containing wastewater according to claim 8, characterized in that: In step c2, the weight of the intermediate C immersed in each liter of the crystallization solution is 120-140 g.

Citation Information

Patent Citations

  • Palladium-copper-rare earth-aluminum oxide catalytic separation composite membrane and preparation method and application thereof

    CN102935335A

  • Preparation method and using method for polyamino / amidoxim-modified multifunctional ion exchange fibers

    CN109289803A

  • Carbon-resistant and sulfur poisoning-resistant solid-state oxide fuel cell positive electrode and preparation method thereof

    CN110061248A

  • Olefin oxidation catalyst and preparation method and application thereof

    CN112569957A

  • Ammonia decomposition catalyst and preparation method and application thereof

    CN115007158A